STUDI PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI KELURAHAN WINANGUN SATU KECAMATAN MALALAYANG KOTA MANADO - Sinjal, Victor J. (HOLISTIK, Journal Of Social and Culture, 2013)
Community participation in development at developing countries is one of the problems that shpuld be studied due to people’s lack of spirit and ability. Poor and powerless condition of the community makes them unable to actively participate in development. The objective of this research is to study community participation and the forms of participation in development in Winangun satu village of malalayang sub district.keywords : participation, development, study